Strategi Pengelolaan Resiko Gagal Panen Untuk Mengurangi Utang Petani Jagung Dalam Perspektif Ekonomi Syariah: (Studi Kasus Desa Padaidi, Kec. Tellusiattinge, Kab. Bone) - Yusdar, Erika Yulistika; Hamzah, Aksi; Rasyid R, Abd. (Metta : Jurnal Ilmu Multidisiplin, 2025)
Agriculture is a vital sector in Indonesia's economy, including in Padaidi Village, Tellu Siattinge Sub-district, Bone Regency, where the majority of the population depends on corn farming for their livelihood. However, farmers in this area often face the risk of crop failure due to extreme weather, pest attacks, and limited access to agricultural technology. This study aims to understand farmers' behavior in facing the risk of crop failure, their debt management strategies during such events, and to review the phenomenon from the perspective of Islamic economics. The method used is descriptive qualitative through interviews, observations, and documentation. The research findings show that farmers’ strategies include business diversification, saving harvested produce, and support from farmer groups. In managing debt, most farmers borrow from middlemen or relatives without interest, yet they still face repayment difficulties due to insufficient harvests. An important finding highlights the need to implement sharia-based contract strategies such as musyarakah, mudharabah, and qardhul hasan, as well as the utilization of Islamic cooperatives and takaful insurance as profit-sharing-based financing models that are fair and effective in reducing farmers’ debt burdens. In conclusion, increasing financial literacy and access to Islamic financial institutions is a strategic step to build farmers’ economic resilience based on Islamic principles.